1990
DOI: 10.1161/01.str.21.6.858
|View full text |Cite
|
Sign up to set email alerts
|

Dementia in stroke survivors in the Stroke Data Bank cohort. Prevalence, incidence, risk factors, and computed tomographic findings.

Abstract: We determined the prevalence of dementia in 927 patients with acute ischemic stroke aged years in the Stroke Data Bank cohort based on the examining neurologist's best judgment Diagnostic agreement among examiners was 68% (K=034). Of 726 testable patients, 116 (16%) were demented. Prevalence of dementia was related to age but not to sex, race, handedness, educational level, or employment status before the stroke. Previous stroke and previous myocardial infarction were related to prevalence of dementia although… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
174
3
3

Year Published

1993
1993
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 238 publications
(191 citation statements)
references
References 26 publications
11
174
3
3
Order By: Relevance
“…138,142,[144][145][146][147] Risk factors for post-stroke dementia At least three different groups of factors, each acting independently, rather than a single pathophysiological mechanism probably contribute to the development of post-stroke dementia: 111,148 (1) stroke-related factors such as the location and the severity of the brain lesions; 149,150 (2) the overall cardiovascular risk profile as determined by the presence of atrial fibrillation 140 or diabetes mellitus; 149 (3) non-strokerelated factors similar to those found in Alzheimer's disease including increasing age, 149,151 low education, 149 cortical atrophy. 145,152 Hypertension has been identified as a risk factor by Pohjasvaara et al (1998), 111 but not by Skoog et al (1996). 101 In addition to those risk factors, coexisting Alzheimer's disease pathology may also play a role, as indicated 146 9.6 Andersen et al, 1996 147 5.5 Kokmen et al, 1996 138 8.4 Hénon et al, 1997 144 16.3 Pohjaasvara et al, 1997 142 12.2…”
Section: Post-stroke Dementiamentioning
confidence: 99%
“…138,142,[144][145][146][147] Risk factors for post-stroke dementia At least three different groups of factors, each acting independently, rather than a single pathophysiological mechanism probably contribute to the development of post-stroke dementia: 111,148 (1) stroke-related factors such as the location and the severity of the brain lesions; 149,150 (2) the overall cardiovascular risk profile as determined by the presence of atrial fibrillation 140 or diabetes mellitus; 149 (3) non-strokerelated factors similar to those found in Alzheimer's disease including increasing age, 149,151 low education, 149 cortical atrophy. 145,152 Hypertension has been identified as a risk factor by Pohjasvaara et al (1998), 111 but not by Skoog et al (1996). 101 In addition to those risk factors, coexisting Alzheimer's disease pathology may also play a role, as indicated 146 9.6 Andersen et al, 1996 147 5.5 Kokmen et al, 1996 138 8.4 Hénon et al, 1997 144 16.3 Pohjaasvara et al, 1997 142 12.2…”
Section: Post-stroke Dementiamentioning
confidence: 99%
“…Taken together, as platelet activation predicts recurrent stroke and previous stroke is the most important predictor of incidence of dementia in stroke survivors in a large stroke cohort (Tatemichi et al, 1990), we investigated the expression of activated fibrinogen receptor and P-selectin on circulating platelets in patients with AD and evaluated their association with cognitive decline in patients with AD after a 1-year follow-up period.…”
Section: Introductionmentioning
confidence: 99%
“…One study found no relation between silent infarcts and PSD (Bornstein et al 1996), but the assessment of the pre-existing cognitive status was not standardized, and the study was underpowered. Other studies clearly identified silent infarcts as independent predictors of PSD (Tatemichi et al, 1990;Desmond et al, 2000;Henon et al, 2001;Pohjasvaara et al, 2000).…”
Section: Neuroimaging Charateristicsmentioning
confidence: 95%
“…In other words, what is the "correct" timing to define "demented" a stroke patient? Tatemichi 21 years ago was the first to put VaD in a temporal context, by observing that 3 months after stroke about one fourth of the patients developed PSD (Tatemichi et al, 1990). Several subsequent studies confirmed this finding, so the time relationship between stroke and cognitive decline was included in the diagnostic criteria for VaD.…”
Section: Timing Of Vascular Dementia (Vad) and Post Stroke Dementia (mentioning
confidence: 99%
See 1 more Smart Citation